Sustainable green catalysis by supported metal nanoparticles - Fukuoka, Atsushi; Dhepe, Paresh Laxmikant (Chemical Record, 2009)
The recent progress of sustainable green catalysis by supported metal nanoparticles is described. The template synthesis of metal nanoparticles in ordered porous materials is studied for the rational design of heterogeneous catalysts capable of high activity and selectivity. The application of these materials in green catalytic processes results in a unique activity and selectivity arising from the concerted effect of metal nanoparticles and supports. The high catalytic performances of Pt nanoparticles in mesoporous silica is reported Supported metal catalysts have also been applied to biomass conversion by heterogeneous catalysis Additionally, the degradation of cellulose by supported metal catalysts, in which bifunctional catalysis of acid and metal plays the key role for the hydrolysis and reduction of cellulose, is also reported. (C) 2009 The Japan Chemical Journal Forum and Wiley Periodicals, Inc. Chem Rec 9: 224-235: 2009: Published online in Wiley InterScience (www.intersciencewiley.corn) DOI 10.1002/tcr.200900004
Keywords: Biomass; cellulose; CO oxidation; Mesoporous silica; supported metal catalyst

In situ encapsulation of Pt nanoparticles in mesoporous silica: synthesis, characterisation and effect of particle size on CO oxidation - Prashar, Atul K.; Mayadevi, S.; Rajamohanan, P. R.; Devi, R. Nandini (Applied Catalysis A-General, 2011)
Pt nanoparticles of narrow size distribution and average particle size of 4.4 nm are isolated exclusively inside SBA-12 mesoporous silica by a novel in situ method. The interaction of Pt precursor with surfactant-polymer composite micelle is followed by NMR and UV studies. The final Pt incorporated silica material is characterised by XRD, TEM and N(2) adsorption. The mesoporous nature of the silica is found to be intact after Pt incorporation without any pore blockage. CO oxidation activity of this material is compared with that of mesoporous silica incorporating different sizes of Pt viz., 1.8, 3.6 and 8 nm. Activation energies of CO oxidation for all these materials are calculated by a simple differential method based on first principles. A comparison of activation energies and single site yields reveals that these parameters are distinguishably less in catalyst containing 1.8 nm Pt nanoparticles but more or less same in catalysts containing 3.6, 4.4 and 8 nm Pt nanoparticles. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; In situ synthesis; Mesoporous silica; Pt nanoparticle

Simple one pot synthesis of nano gold-mesoporous silica and its oxidation catalysis - Sekhar, A. C. Sunil; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Today, 2012)
A simple one pot synthesis strategy using a non ionic triblock copolymer P123 as reducing as well as templating agent has been employed to prepare nano gold particles incorporated in the pores of mesoporous silica catalyst. The catalyst is characterized by XRD, nitrogen adsorption desorption isotherms at 77 K and TEM. The presence of small gold nanopartilces (similar to 2-4 nm) clearly demonstrated that this strategy can be effective in incorporating Au inside mesochannels. The catalyst reduced at 300 degrees C in H-2 was found to be active for oxidation reactions, such as CO oxidation, and benzyl alcohol. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Alcohol oxidation; CO oxidation; Gold catalysis; Mesoporous silica

Functional and disordered meso-macroporous gamma-Al2-xMxO3 +/- y (M = Cu and/or Ce) - Gnanakumar, Edwin S.; John, Jino C.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2013)
Disordered meso-macro porous Cu-Ce-Al2O3 nanocomposite (gamma-Al2-xMxO3 +/- y, M = Cu and or Ce) with different compositions has been synthesized. In situ templated sol-gel method has been adopted with simple EDTA ethylenediamine tetra aceticacid and ethylenediamine molecules to prepare gamma-Al2-xMxO3 +/- y, (M = Cu and or Ce). Above meso-macro porous materials were characterized by structural, spectroscopy, microscopy and textural techniques. Detailed characterization indicates that Cu2+ ions are introduced into the ceria and alumina lattice positions. Nano composite nature of the gamma-Al2-xMxO3 +/- y has been confirmed by detailed microscopy investigations. Catalytic activity of the above nanocomposite materials have been screened for environmentally important CO oxidation reaction. 30% Ce-60% Al and 10% Cu containing material shows the best activity among other meso-nnacroporous material with (50%) 100% CO oxidation at (107 degrees C) 145 degrees C.
Keywords: Alumina; CO oxidation; heterogeneous catalysis; Meso-Macroporous Material; Nanocomposite; Sol-gel synthesis

Oxidation catalysis by large trisoctahedral gold nanoparticles: Mind the step! - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Catalysis Today, 2015)
To understand the origin of catalysis by gold and to probe the role of defects and interfaces, benchmark reactions namely CO oxidation and benzyl alcohol oxidation were carried out on supported trisoctahedral gold nanoparticles and on the inverse catalyst system. The sizes of these particles which are between 45 nm and 110 nm, are well beyond the quantum size regime and well above the optimum size range where gold is considered to be catalytically active. The periodic steps sites in contact with oxide support interface were able to promote the reaction. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; Defects; Gold catalysis; Inverse catalysta; Steps and kinks

CO oxidation on large high-index faceted Pd nanostructures - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Journal of Catalysis, 2016)
The structure sensitivity of CO oxidation has been investigated on oxide-supported palladium nanoparticles of different morphologies. The reactivity of concave nanocubes and nanoflowers that expose {3 1 0} and {3 1 1} high-index facets showed a lower onset temperature for CO oxidation than Pd nanospheres of size around 6 nm. These concave nanocubes and nanoflowers were also found to catalyze the CO oxidation reaction more efficiently than simple cubes and spheres of similar size that exposed low-index facets. The enhanced activity of these nanoparticles compared with other morphologies are attributed to the presence of sites of under-coordination on the exposed high-index facets. The larger nanoparticles were also found to be more stable in the reaction environment. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: CO oxidation; High-index facets; Pd nanoparticles; structure sensitivity

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

Low-temperature preferential CO oxidation in a hydrogen-rich stream over Pt-NaY and modified Pt-NaY catalysts for fuel cell application - Malwadkar, Sachin; Bera, Parthasarathi; Satyanarayana, Chilukuri V. V. (Fuel Cells, 2023)
Preferential oxidation of CO (CO-PROX) in the hydrogen-rich stream has been carried out over Pt-NaY catalysts containing various Pt loadings along with Fe, Co, and Au. Catalysts have been characterized with inductively coupled plasma-atomic emission spectroscopy, Brunauer, Emmett, and Teller surface area, X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, temperature programmed reduction, and Pt dispersion. CO-PROX activities and CO oxidation selectivities are observed to increase with an increase in Pt content. Pt-NaY catalyst with 0.75 wt.% Pt loading shows maximum CO-PROX activity at low temperatures. An increase in space velocity decreases the CO and O-2 conversions, but CO oxidation selectivity increases. A decrease in activity is observed when reformat gas contains around 20% H2O. During the stability test, no change in CO and O-2 conversions is observed, but a small increase in the CO oxidation selectivity is noticed after 10 h indicating that the Pt-NaY catalyst is a promising candidate for CO-PROX reaction in a hydrogen-rich stream. The Pt-Fe-NaY catalyst shows better activity than the Pt-NaY catalyst but starts deactivating after 10 h. However, activity is observed to decrease over Pt-Co-NaY and Pt-Au-NaY catalysts. Pt-Fe-NaY catalyst with 0.75 and 0.35 wt.% Pt and Fe, respectively, shows better CO-PROX activity at a temperature of 75 degrees C.
Keywords: catalysis; CO oxidation; experimental results; flow bed; Fuel Cell Applications; Hydrogen; X-ray photoelectron spectroscopy

Atmospheric-pressure continuous-flow methane oxidation to methanol and acetic acid using H2O2 over the Au-Fe catalyst - Jagtap, Anuradha V.; Kumar, Pawan; Gupta, Sharad; Nagendra, Abharana; Jha, Shambhu Nath; Bhattacharyya, D.; Ajithkumar, Thalasseril G.; Vinod, C. P. (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: CO oxidation; HIGHLY SELECTIVE OXIDATION; metal-organic frameworks

Remarkable SO2 and H2S resistant ability on CO oxidation by unique Pd/WO3 3D hollow sphere nanocatalyst: correlating structure-activity relationships on SO2 exposure - Jeyavani, Vijayakrishnan; Kondhekar, Deepali; Bhati, Meema; Dev, Sahil; Joshi, Kavita; Devi, R. Nandini; Mukherjee, Shatabdi Porel (ACS Applied Energy Materials, 2024)
We report a simple inorganic route for synthesizing a Pd/WO3 3D hollow sphere nanocatalyst, where Pd nanoparticles are encapsulated and well distributed on porous tungsten oxide nanospheres. The synthesis protocol has advantages, as it requires no surfactant or stabilizing agent, Pd loading is easily tuned, and the as-synthesized nanomaterials can be directly used as catalysts for the CO oxidation reaction. The synthesized nanocatalyst exhibited 100% CO to CO2 conversion efficiency at 260 degrees C. In addition, the nanocatalyst demonstrated remarkable SO2 (3 ppm) tolerance during the CO oxidation reaction for prolonged SO2 sulfation of 1-21 h at 260-400 degrees C. This represents the longest SO2 exposure time reported to date based on a single metal Pd/support-based nanocatalyst. No decrement in CO conversion efficiency was observed even after SO2 (3 ppm) treatment for 21 h for the first time based on a single metal Pd-based nanocatalyst. Moreover, the synthesized nanocatalyst shows H2S (4 ppm), even in situ H2S tolerance during the CO oxidation reaction at 260 degrees C for 1-3 h and exhibited less sensitivity to prolonged and stringent sulfur exposure, with the highest H2S concentration and maximum 100% CO to CO2 conversion efficiency obtained after H2S treatment for the first time based on a Pd-based nanocatalyst to the best of our knowledge. The composition and structure of the R-Pd/WO3 nanocatalyst were not much influenced, even after the prolonged SO2 and H2S exposure during the CO oxidation reaction, as verified from spent catalyst analysis. Finally, our DFT-based model provides insights into understanding the observed sulfur resistance on Pd/WO3 by analyzing the underlying electronic structure. Therefore, our strategic synthesis methodology will open up many opportunities to select Pd/metal oxide-based nanomaterials for designing highly efficient, stable, and SO2/H2S-resistant nanocomposite catalyst.
Keywords: CO oxidation; DFT calculation; nanocatalyst; palladium (Pd); SO2 andH(2)S resistant ability; structure-activityrelationships; tungstenoxide (WO3)